Construction and systematic assessment of relative deformation histories - Potts, G.; Reddy, Steven (Elsevier, 1999)
The systematics of deformation histories have been investigated using basic combinatorial mathematics. Using this approach, the number of deformation histories and the number of relationships associated with a given number of structures can be calculated. The range of possible deformation histories can also be determined. Using this information, the ambiguous nature of all deformation histories is examined together with the impact of unobserved relationships. The number of possible deformation histories that are compatible with a collection of age relationships is used as a crude measure of confidence in those histories. A procedure is described for the construction of deformation histories that is systematic, repeatable and rapid and within which ambiguities can be easily recognised.